Oxygen therapy in ST-elevationmyocardial infarction - Hofmann, Robin; Witt, Nils; Lagerqvist, Bo; Jernberg, Tomas; Lindahl, Bertil; Erlinge, David; Herlitz, Johan; Alfredsson, Joakim; Linder, Rikard; Omerovic, Elmir; Angerås, Oskar; Venetsanos, Dimitrios; et al. (European heart journal, 2018)
Aims To determine whether supplemental oxygen in patients with ST-elevation myocardial infarction (STEMI) impacts on procedure-related and clinical outcomes. Methods and results The DETermination of the role of Oxygen in suspected Acute Myocardial Infarction (DETO2X-AMI) trial randomized patients with suspected myocardial infarction (MI) to receive oxygen at 6 L/min for 6-12 h or ambient air. In this pre-specified analysis, we included only STEMI patients who underwent percutaneous coronary intervention (PCI). In total, 2807 patients were included, 1361 assigned to receive oxygen, and 1446 assigned to ambient air. The pre-specified primary composite endpoint of all-cause death, rehospitalization with MI, cardiogenic shock, or stent thrombosis at 1 year occurred in 6.3% (86 of 1361) of patients allocated to oxygen compared to 7.5% (108 of 1446) allocated to ambient air [hazard ratio (HR) 0.85, 95% confidence interval (95% CI) 0.64-1.13; P = 0.27]. There was no difference in the rate of death from any cause (HR 0.86, 95% CI 0.61-1.22; P = 0.41), rate of rehospitalization for MI (HR 0.92, 95% CI 0.57-1.48; P = 0.73), rehospitalization for cardiogenic shock (HR 1.05, 95% CI 0.21-5.22; P = 0.95), or stent thrombosis (HR 1.27, 95% CI 0.46-3.51; P = 0.64). The primary composite endpoint was consistent across all subgroups, as well as at different time points, such as during hospital stay, at 30 days and the total duration of follow-up up to 1356 days. Conclusions Routine use of supplemental oxygen in normoxemic patients with STEMI undergoing primary PCI did not significantly affect 1-year all-cause death, rehospitalization with MI, cardiogenic shock, or stent thrombosis.